2011
DOI: 10.1099/jmm.0.027169-0
|View full text |Cite
|
Sign up to set email alerts
|

Weissella confusa: a rare cause of vancomycin-resistant Gram-positive bacteraemia

Abstract: We describe a case of bacteraemia caused by Weissella confusa in a 48-year-old male who was operated on for adenocarcinoma of the gastro-oesophageal junction and maintained on total parenteral nutrition. Blood cultures were positive for a vancomycin-resistant streptococcus-like organism which was identified as W. confusa by 16S rRNA gene sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…W. cibaria and W. viridescens have been associated with bacteremia [18] and W. cibaria and W. confusa have been also isolated from dog ear otitis [37]. Concerning W. confusa, several cases reported bacteremia and infections [196][197][198][199][200][201][202][203][204][205][206]. In almost all cases of infections associated W. confusa, patients were immunocompromised or have undergone chemotherapy or organ transplant [207].…”
Section: Infections Associated With Weissellamentioning
confidence: 99%
“…W. cibaria and W. viridescens have been associated with bacteremia [18] and W. cibaria and W. confusa have been also isolated from dog ear otitis [37]. Concerning W. confusa, several cases reported bacteremia and infections [196][197][198][199][200][201][202][203][204][205][206]. In almost all cases of infections associated W. confusa, patients were immunocompromised or have undergone chemotherapy or organ transplant [207].…”
Section: Infections Associated With Weissellamentioning
confidence: 99%
“…It has been generally agreed that Weissella confusa grow in different ecological habitat but it is more commonly found in sugarcane juice, milk, fermented foods and human samples [17]. It has already been stated that Weissella kimchi PL9023 is a potential probiotic for women because the species produces high amount of hydrogen peroxide (H 2 O 2 ) amongst most of the LAB and it has been reported that the species inhibit the growth and the adherence of the vaginal isolates of Candida albicans, Escherichia coli, Staphylococcus aureus and Streptococcus agalacitiae [11].…”
Section: Disscussionsmentioning
confidence: 99%
“…Weissella confusa (formerly Lactobacillus confusus) has been isolated from a variety of sources: sugar cane, carrot juice, milk, fermented foods and beverages, and human and animal samples (2,3,6,9). It is more particularly found in many fermented cereals and vegetables (2,3,6).…”
mentioning
confidence: 99%